2011
DOI: 10.1007/s11357-011-9336-z
|View full text |Cite
|
Sign up to set email alerts
|

Aging and vascular dysfunction: beneficial melatonin effects

Abstract: Aging is characterized by a progressive deterioration of physiological functions and metabolic processes. In aging and in diseases associated with the elderly, the loss of cells in vital structures or organs may be related to several factors. Sirtuin1 (SIRT1) is a member of the sirtuin family of protein deacetylases involved in life span extension; however, its involvement in the aging is not yet completely defined. Recently, melatonin, a pleiotropic molecule, shown to activate SIRT1 in primary neurons of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 64 publications
(69 reference statements)
0
39
0
Order By: Relevance
“…In a previous study, our research group indicated that the SIRT1-p53-NO axis may be one of the fundamental determinants of advancing endothelial dysfunction linked to aging and underlined the role of SIRT1 as a driver of cellular stress resistance and longevity. In particular, we observed that melatonin, pineal indoleamine which is known to be decreased during aging as well (Bubenik and Konturek 2011;Reiter et al 2002), increases SIRT1 expression and improves cellular survival at the aorta level of apolipoprotein E null mice, thereby reducing the progression of atherogenesis (Rodella et al 2013). SIRT1 may also prevent atherothrombosis by downregulating the endothelial expression of tissue factors; in fact, treatment of wild-type mice with the SIRT1 inhibitor in vivo enhanced tissue factor activity and markedly reduced the coagulation time in a photochemical vascular injury model (Breitenstein et al 2011).…”
Section: The Sirtuin Familymentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, our research group indicated that the SIRT1-p53-NO axis may be one of the fundamental determinants of advancing endothelial dysfunction linked to aging and underlined the role of SIRT1 as a driver of cellular stress resistance and longevity. In particular, we observed that melatonin, pineal indoleamine which is known to be decreased during aging as well (Bubenik and Konturek 2011;Reiter et al 2002), increases SIRT1 expression and improves cellular survival at the aorta level of apolipoprotein E null mice, thereby reducing the progression of atherogenesis (Rodella et al 2013). SIRT1 may also prevent atherothrombosis by downregulating the endothelial expression of tissue factors; in fact, treatment of wild-type mice with the SIRT1 inhibitor in vivo enhanced tissue factor activity and markedly reduced the coagulation time in a photochemical vascular injury model (Breitenstein et al 2011).…”
Section: The Sirtuin Familymentioning
confidence: 98%
“…SIRT1 may also prevent atherothrombosis by downregulating the endothelial expression of tissue factors; in fact, treatment of wild-type mice with the SIRT1 inhibitor in vivo enhanced tissue factor activity and markedly reduced the coagulation time in a photochemical vascular injury model (Breitenstein et al 2011). SIRT1 may be a potential target for the intervention on VSMC hypertrophy age-associated vascular disease, even if the mechanism are actually not well defined (Danz et al 2009;Guarani and Potente 2010;Li et al 2011;Rodella et al 2013).…”
Section: The Sirtuin Familymentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were not observed when the animals had been initially administrated (for 2-3 weeks) МТ (5 mg/kg) [42]. In a strain of mice with apolipoprotein E deficiency that simulated age-associated hypertension, a repeated use of МТ eliminated adverse hemodynamic changes, the metabolic dysfunction and other associated aberrations in the vessel cytoarchitectonics [69].…”
mentioning
confidence: 99%
“…), accumulation of glutathione and so on. [38,58,70]. Actually, the limitation of oxidative stress that takes place actually under any cerebral and visceral pathology is viewed as the leading mechanism that lays the basis for both common and unique protective effects of MT [3,65].…”
mentioning
confidence: 99%